2014
DOI: 10.3791/51276
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Dendritic Spines of Rat Primary Hippocampal Neurons using Structured Illumination Microscopy

Abstract: Dendritic spines are protrusions emerging from the dendrite of a neuron and represent the primary postsynaptic targets of excitatory inputs in the brain. Technological advances have identified these structures as key elements in neuron connectivity and synaptic plasticity. The quantitative analysis of spine morphology using light microscopy remains an essential problem due to technical limitations associated with light's intrinsic refraction limit. Dendritic spines can be readily identified by confocal laser-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…50 thousand hippocampal NSPC were seeded per well in 24-well plates containing poly-L-lysine and Laminin coated glass coverslips as described before 68 . The next day cells were transfected with FLAG-tagged human BCL2L13, a kind gift from Dr. Jürg Tschopp, Institute of Biochemistry, University of Lausanne (Kataoka et al , 2001), using Attractene (Qiagen) or empty vector and were incubated for 48 h. In the last 7 h of the incubation cells were treated with varying concentrations of KA ranging from 0–300 μM KA or vehicle 46 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 thousand hippocampal NSPC were seeded per well in 24-well plates containing poly-L-lysine and Laminin coated glass coverslips as described before 68 . The next day cells were transfected with FLAG-tagged human BCL2L13, a kind gift from Dr. Jürg Tschopp, Institute of Biochemistry, University of Lausanne (Kataoka et al , 2001), using Attractene (Qiagen) or empty vector and were incubated for 48 h. In the last 7 h of the incubation cells were treated with varying concentrations of KA ranging from 0–300 μM KA or vehicle 46 .…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, cells were stained with polyclonal sheep anti-CytC (Sigma-Aldrich, 1:100) in combination with donkey anti-sheep Alexa488 (Invitrogen, 1:1000) and coverslips were mounted in vectashield mounting medium (Vector Labs). SIM was performed using a Nikon Eclipse Ti inverted microscope based SIM system as described before 68 .…”
Section: Methodsmentioning
confidence: 99%
“…To better define the various spine types, the images of dendritic spines were acquired using Super-resolution Structured Illumination Microscopy (SR-SIM), which has about 2-fold higher axial resolution than confocal microscopy (42) and is suitable for visualization of cellular structures around 200 nm, such as the neck of a dendritic spine (see supplemental Fig. S2) (43). We found that STRN4 expression differed in distinct subtypes of dendritic spines, with the highest STRN4 immunoreactivity present in stubby spines and the spine heads of mushroomshaped spines that contained PSD-95 clusters, whereas STRN4 immunoreactivity was significantly reduced in thin spines and filopodia (Fig.…”
Section: Strn4 Is Expressed Preferentially In Mushroom and Stubby Spinesmentioning
confidence: 99%
“…59 What's more, Schouten et al also identi¯ed dendritic spines of rat primary hippocampal neurons using SIM and analyzed the spines morphology quantitatively. 60 Because of the characteristics of PALM/STORM algorithm, this super-resolution microscopy is convenient for monitoring the structure of axons. Zhuang et al used STORM to observe the development of axons and revealed the mechanism of actin, spectrin, and associated molecules forming a periodic sub-membrane lattice structure in axons.…”
Section: Applications In Neurosciencementioning
confidence: 99%